What is love? - Comfort, Jen (Montlake, 2024)
What is love? Answer: From the Latin word for crossroads, this is knowledge so common as to be obscure, the pursuit of which engages millions daily. Question: What is trivia? Trivia is the magic in the mundane, the connection in the commonplace, and Maxine Hart's second-favorite pastime. A self-proclaimed Brooklyn street rat and a high school dropout, Maxine has never been a fan of formal education, but thanks to her ADHD "superpowers," she's a glutton for knowledge--and a good fight. And when Maxine enters the trivia game show Answers!, her brilliance, coupled with her penchant for big bets, devastates her competition. Even record-holding, 76-time-winner Teddy Ferguson. Or was it their kiss the night before they faced off that threw the buttoned-up professor off his game? Now, Maxine and Teddy cross paths again in a high-stakes tournament against all-time Answers! winners, including undefeated champion Hercules McKnight. With nothing in common but an insatiable appetite for knowledge and a desire to win, Maxine offers Teddy a deal: combine their strengths to shore up their weaknesses. She'll push his tolerance for risk and improve his buzzer speed, if he'll find creative ways to fill in the gaps in her education. Except neither one of them foresaw just how scintillating learning could be...